PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL TAI (TEAM ASSISTED INDIVIDUALIZAION) BERBANTUAN CD INTERAKTIF PADA SISWA SEKOLAH DASAR - Aries Tika Damayani; Intan Rahmawati; Kiswoyo . (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
The purpose of this research is to develop mathematical learning devices using models TAI (Team Assisted Individualizaion) bernantuan interactive CD on elementary school students. This research is the development research, with the learning of mathematics using the model of TAI (Team Assisted Individualizaion) bernantuan interactive CD developed and tested can deliver students achieve KKM. Based on the value of learning research class average is 74 and 67, classical completeness reached 85% and 76%. Although the classical completeness is high, there are still some students who have high levels of learning achievement are different. Results of the questionnaire responses of students in the learning device models that use the TAI is very good and can be used. They were very enthusiastic about the show high activity especially with an interactive CD-assisted learning with the bias make students interested and excited to learn. Math learning tools developed include lesson plans, interactive CD, achievement test is valid according to experts, the results of the validation study by three validator showed good results. Mathematics learning devices using models TAI (Team Assisted Individualization) assisted interactive CD developed to be effective due to complete in achievement test and no influence on the test results of learning activities. Keywords: Learning Mathematics, TAI, Interactive CD